National Regulation of Space Activities
XXVIII, 500 p.
Keywords: This book comprehensively addresses all aspects of national space laws and regulations governing the conduct of space activities in fifteen space-faring nations. This is the first book of its kind that contains a compilation of materials written from a neutral and objective perspective by the world’s leading space law experts selectively drawn from the fifteen countries whose laws and regulations are covered by the book. In order to provide the reader with a full understanding and appreciation of the various relevant national laws and regulations that govern space activities, this book explores the policies and rationales underlying the law, constitutional basis for the adoption of national space laws, some facts about national space activities in the respective countries, and as well, discusses the relevant principles and rules of international space law in order to bring to light the international context of the national laws described. Since the U.S. presently has the most developed and extensive regime of national space laws and regulations, six chapters of this book are devoted to a thorough examination of those laws and regulations. The unique feature of this compilation is that, apart from the description of applicable national laws and regulations on space activities that it provides, it also sets out the various procedures to be followed particularly by domestic and foreign private entities in order to achieve compliance with the numerous and varied national legal requirements concerning space activities. This work will be a valuable resource not only to students, researchers and academics in the fields of space law and regulation, but also to space industry executives, specialist lawyers, foreign ministries as well as international organizations, such as the United Nations.